"Diseño de un sistema de gestión de seguridad y salud rn rl trabajo, basado en la decisión 584 instrumento andino de seguridad y salud en el trabajo; para la industria maderera Izquierdo Aguilera INMAI S..A." - Pila Méndez, Adonis Alfredo (2018)
The Industry INMAIA S.A. is in the field of industrial safety, the occasion, is produced, produced, reduced, shown, in the field of safety. a Security Management System, to comply with the legal requirements and the norm of the subject of Health and Safety at Work Improving Competitiveness in the Wood Market. In this thesis, the reader, a description of the industrial activities carried out by INMAIA SA, in its industrial plant, the results of the tasks are analyzed causes accidents or occupational diseases. For example, this is the degree of compliance of the company in the Occupational Health and Safety System, as a result of this verification the company complies with 22.60%, this rating being insufficient to demonstrate good management by the company, Therefore, it is about creating a Security Management System, according to the model of Ecuador and is committed to implement the recommended model in all the elements that make up the administrative, technical, human and control procedures.